2002
DOI: 10.1093/jn/132.6.1345
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Folate, Vitamin B-12 or Vitamin B-6 Supplementation Slightly Affects Memory Performance But Not Mood in Women of Various Ages

Abstract: Based on research demonstrating associations between folate, B-12 and B-6 vitamins and cognition and mood, we investigated the effects of short-term supplementation in 211 healthy younger, middle-aged and older women who took either 750 microg of folate, 15 microg of vitamin B-12, 75 mg of vitamin B-6 or a placebo daily for 35 d. In addition, we examined associations between dietary intake of these vitamins and cognition and mood. Usual dietary intake status was estimated using a retrospective, self-report, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 56 publications
5
176
0
5
Order By: Relevance
“…[1][2][3] Vitamin B 6 has been shown to be important for normal cognitive function and in lowering the incidence of coronary heart disease among the elderly. [4][5][6] In addition, vitamin B 6 supplementation has been shown to reduce diabetic complications and incidences of neurodegenerative diseases in varying degrees. [4][5][6][7][8] Vitamin B 6 refers to three primary forms of water-soluble vitamins: pyridoxine, pyridoxal phosphate, and pyridoxamine.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Vitamin B 6 has been shown to be important for normal cognitive function and in lowering the incidence of coronary heart disease among the elderly. [4][5][6] In addition, vitamin B 6 supplementation has been shown to reduce diabetic complications and incidences of neurodegenerative diseases in varying degrees. [4][5][6][7][8] Vitamin B 6 refers to three primary forms of water-soluble vitamins: pyridoxine, pyridoxal phosphate, and pyridoxamine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research provides evidence for a positive relationship between homocysteine and depression 30,31 , a relationship which appears to become stronger as plasma homocysteine levels increase. Contrary to what previous research would suggest, homocysteine was not found to be associated with mood in this sample of healthy males.…”
Section: Discussionmentioning
confidence: 95%
“…A close negative correlation was found in the elderly between cognitive abilities, high homocysteine as well as low vitamin B 6 levels. With doses of vitamin B 6 (20 mg/day) exceeding RDA values (1.7 mg/day), a definite improvement was observed regarding the memory-related abilities of elderly people aged 70-79 years (Bryan et al, 2002).…”
Section: Vitamin Bmentioning
confidence: 94%